Comparative Analysis of Indonesia Cities Sector Competitiveness: Case Study of Cities in North Sulawesi Province 2017-2021 - Rorong, Ita P. F.; Mauna T.B. Maramis; Honny Kansil; Sifra Sendow; Refinna C. Jacobus (HM Publisher, 2023)
The main problem in regional development lies in human and natural resources and is seen from the potential that exists and is owned in an area to increase the number and type of job opportunities for the community in the area itself. Economic development is a process. The process in question is a process that includes the formation of new institutions, the development of alternative industries, improving the capacity of the existing workforce to produce better products and services, identifying new markets, transferring knowledge, and developing new companies. This study aims to compare the competitiveness of the economic sectors of 4 cities in North Sulawesi province. The data used in this study are secondary data obtained based on available data and sourced from reports from the Central Bureau of Statistics. The data included in this research is gross domestic, regional product (GRDP) data at constant prices for 2017-2021. The objects are Manado, Tomohon, Bitung and Kotamobagu. By using the location quotient analysis method, shift share, and Klassen typology. The findings of the research show that the sectors that have competitiveness in the economy of 4 cities in North Sulawesi province are the processing industry, electricity and gas procurement, water procurement, waste management, waste and recycling, construction, wholesale, and retail trade; car and motorcycle repair, transportation and warehousing, provision of accommodation and food and drink, information and communication, financial and insurance services, company services, government administration, defense and compulsory social security and education services and health services. In conclusion, Manado is the city with the highest sector development and growth values compared to Tomohon, Bitung, and Kotamobagu.